Historical development and current status of organ procurement from death-row prisoners in China. Issue 1 (December 2015) - Allison, Kirk; Caplan, Arthur; Shapiro, Michael; Els, Charl; Paul, Norbert; Li, Huige
Abstract Background In December 2014, China announced that only voluntarily donated organs from citizens would be used for transplantation after January 1, 2015. Many medical professionals worldwide believe that China has stopped using organs from death-row prisoners. Discussion In the present article, we briefly review the historical development of organ procurement from death-row prisoners in China and comprehensively analyze the social-political background and the legal basis of the announcement. The announcement was not accompanied by any change in organ sourcing legislations or regulations. As a fact, the use of prisoner organs remains legal in China. Even after January 2015, key Chinese transplant officials have repeatedly stated that death-row prisoners have the same right as regular citizens to "voluntarily donate" organs. This perpetuates an unethical organ procurement system in ongoing violation of international standards. Conclusions Organ sourcing from death-row prisoners has not stopped in China. The 2014 announcement refers to the intention to stop the use of organs illegally harvested without the consent of the prisoners. Prisoner organs procured with "consent" are now simply labelled as "voluntarily donations from citizens". The semantic switch may whitewash sourcing from both death-row prisoners and prisoners of conscience. China can gain credibility only by enacting new legislation prohibiting use of prisoner organs and by making its organ sourcing system open to international inspections. Until international ethical standards are transparently met, sanctions should remain.